Pemanfaatan Kiasan “Budi” Didalam Bahasa Minangkabau - Adriyetti Amir; Aslinda Aslinda; Genta Gempita; Harry Ramza (Penerbit Kemala Indonesia, 2016)
Kieh or kiasan is seldom used in Minangkabau language. It is defined as prefix world and inserted for senses of giving on the sentence and stressing word as important meaning. Sentence style uses the equality performa, comparative, short sequential story, to explanation of morals and ethics, to describe of static materials or something else that it have the human souls, to give the same place and people, to show name and behavior, to apply the words that addressed on the other sentences and also many other style of language. In Minangkabau language, kiasan is one thing that is applied in every heart condition of speakers. This paper describes application of “Budi” word in Minangkabau language. It can be refer of human behavior on formal/non-formal frame ideas of Minangkabau speaker and word samples are also presented.